SOCIETAL-SPECIFIC FACTORS RELATED TO ADHERENCE TO ROUTINE NON-PHARMACOLOGIC INTERVENTIONS AMONG PATIENTS WITH CHRONIC ILLNESSES ATTENDING LUWEERO HEALTH CENTER IV. - Nakimera, Irene; Serunjogi, David (Student's Journal of Health Research Africa, 2024)
Background: The study aims to determine societal-specific factors related to adherence to routine non-pharmacologic interventions among patients with chronic illnesses attending Luweero HC IV. Methodology: A cross-sectional survey design using questionnaires was adopted to collect data from 326 patients with chronic illnesses visiting Luweero Health Centre IV. This district is located approximately 47 miles from north Kampala. This center was chosen based on the number of patients having chronic illnesses, attending and receiving services. A simple random sampling technique was used to select patients, and only those who met inclusion criteria were interviewed. Purposive sampling was used to select 5 health professionals in charge of chronic illnesses. Results: Out of the 326 patients who participated in the study, adherence to routine non-pharmacologic interventions due to societal-specific factors was lowest (33.3%) amongst patients with cultural beliefs and highest (74.4%), amongst patients who have no cultural beliefs, highest (61.0%) amongst patients who believed that non-pharmacological treatment takes long, unlike amongst patients whose belief is that herbs and traditionalist treat best 36.2%. The lowest among patients whose cultural practices are ritual performances done on patients by traditionalists is 43.2% and the highest amongst patients whose cultural practice is taking herbs is 78.8%. Conclusion: All societal factors at multivariate analysis were found to have an impact on adherence to routine non-pharmacological interventions. Recommendation: Non-pharmacologic interventionists to design and institute group visiting mechanisms, especially among patients who are unmarried if routine adherence is to be improved.